Auditory Evoked Potentials for the Evaluation of Hearing Sensitivity in Navy Dolphins. Modification P00002: Assessment of Hearing Sensitivity in Adult Male Elephant Seals - Houser, Dorian S. (2006)
A custom auditory evoked potential (AEP) system was used to assess the feasibility of rapidly testing the hearing of bottlenose dolphins by tracking the magnitude of the envelope following response (EFR). Tests were conducted in-air (N=4) and on submerged dolphins (N=3) for which behavioral audiograms had been obtained in San Diego Bay or a quiet above ground pool. For in-air AEP measurements, differences between AEP and pool behavioral thresholds increased with threshold magnitude and ranged from 0 to +18 dB. For underwater AEP measurements, differences between AEP and pool behavioral thresholds varied from -10 to 9 dB. After benchmarking the AEP approach, AEP thresholds were obtained from 42 dolphins housed at the Navy Marine Mammal Program. Animals ranged from 4 to 47 years of age and consisted of 28 males and 14 females. Consistent with other mammalian systems, the range and sensitivity of hearing declined with age with onset typically occurring between the ages of 20 and 30. Males generally exhibited hearing loss at a younger age than female dolphins. The AEP system was subsequently applied to the northern elephant seal (Mirounga angustirostris) to determine how to adapt AEP approaches to larger animals with less robust auditory systems. The original document contains color images.